Internal Quality Audit Information System at Saint Thomas Catholic University - Fanni Maria Dortua Tampubolon; Paska Marto Hasugian (INFOKUM, 2026)
This study aims to develop a web-based Internal Quality Audit Information System (SIAMI) at the Quality Assurance Agency of Santo Thomas Catholic University to support the implementation of Internal Quality Audits (AMI), which were previously conducted manually using separate media such as spreadsheets, email, WhatsApp, Google Drive, and printed documents. These conditions caused inefficiencies in document management, audit implementation, audit result recapitulation, and monitoring of Corrective Action Plans (RTL). The system was developed using the Rapid Application Development (RAD) method, which consists of Requirement Planning, User Design, Construction, and Cutover stages. Data were collected through interviews, documentation, and literature studies to identify system requirements based on the internal audit business process. The application was developed using PHP as the programming language and MySQL as the database management system, while Unified Modeling Language (UML) was employed for system modeling. The results show that SIAMI successfully integrates all stages of the Internal Quality Audit process, including audit instrument management, auditor assignment, evidence document submission, audit implementation, audit result recapitulation, Management Review Meetings (RTM), Corrective Action Plans (RTL), and follow-up verification within a single web-based platform. The developed system improves the effectiveness, efficiency, and accuracy of audit data management while facilitating monitoring and evaluation activities to support continuous quality improvement at Santo Thomas Catholic University.